Ant and Honey Bee a pair of friends in winter - McDonald, Megan; Karas, G. Brian (Somerville, Massachusetts Candlewick Press, 2013)
The funny, endearing insect pals find a way to be more than fair-weather friends in a second early chapter book from Megan McDonald and G. Brian Karas. "Brrrr!" The leaves are off the trees, and frost is on the ground. It's time for bugs to hunker down and hide out for the winter. But Ant isn't ready to hunker down. Ant isn't ready to be "all by herself" for months on end. The thought of a long chilly season without her best friend, Honey Bee, is enough to make Ant shiver with dread. Can Ant brave the cold for one last surprise visit before the snow flies? And will Honey Bee welcome an interruption of her peace and quiet? The author of the Judy Moody series teams up again with award-winning illustrator G. Brian Karas to show that true friends can weather whatever comes their way -- even if one is feeling antsy and the other has blissful hibernation in mind
Dark days -- EEP OT -- Peanut butter and jelly
Keywords: Ants -- Juvenile fiction; Bees -- Juvenile fiction; Friendship -- Juvenile fiction; Honeybee -- Juvenile fiction; Winter -- Juvenile fiction; Winter -- Fiction